Design fuzzy logic controller on ball and beam system / Bibi Sarpinah Sheikh Naimullah - Sheikh Naimullah, Bibi Sarpinah (1998)
The purpose of this project is to developed a fuzzy logic controller for ball and beam system. Formerly, PID (Proportional plus Integrative plus Derivative) controller was used and this project will investigate the possibility of applying fuzzy controller in the system. The aim of the ball and beam experiment in this project is to control the position of the ball along the track by manipulating the angular position of the servo. The rolling ball should be balanced on the beam. The motor controls the beam angle. The designing of fuzzy logic controller was based on Fuzzy-TECH software. FuzzyTECH generated the response of the output by applying as C code or M code that can be generated easily. In this project, the output is generated as M code. The performance of fuzzy logic controller was also compared with the PID controller. The best controller will be proved in the end of this project.